North Atlantic Oscillation drives the annual occurrence of an isolated, peripheral population of the brown seaweed Fucus guiryi in the Western Mediterranean Sea - Melero-Jiménez,Ignacio J.; Salvo,A. Enrique; Báez,José C.; Bañares-España,Elena; Reul,Andreas; Flores-Moya,Antonio (PeerJ, 2017)
The canopy-forming, intertidal brown (Phaeophyceae) seaweed Fucus guiryi is distributed along the cold-temperate and warm-temperate coasts of Europe and North Africa. Curiously, an isolated population develops at Punta Calaburras (Alboran Sea, Western Mediterranean) but thalli are not present in midsummer every year, unlike the closest (ca. 80 km), perennial populations at the Strait of Gibraltar. The persistence of the alga at Punta Calaburras could be due to the growth of resilient, microscopic stages as well as the arrival of few–celled stages originating from neighbouring localities, and transported by the permanent Atlantic Jet flowing from the Atlantic Ocean into the Mediterranean. A twenty-six year time series (from 1990 to 2015) of midsummer occurrence of F. guiryi thalli at Punta Calaburras has been analysed by correlating with oceanographic (sea surface temperature, an estimator of the Atlantic Jet power) and climatic factors (air temperature, rainfall, and North Atlantic Oscillation –NAO-, and Arctic Oscillation –AO- indexes). The midsummer occurrence of thalli clustered from 1990–1994 and 1999–2004, with sporadic occurrences in 2006 and 2011. Binary logistic regression showed that the occurrence of thalli at Punta Calaburras in midsummer is favoured under positive NAO index from April to June. It has been hypothesized that isolated population of F. guiryi should show greater stress than their congeners of permanent populations, and to this end, two approaches were used to evaluate stress: one based on the integrated response during ontogeny (developmental instability, based on measurements of the fractal branching pattern of algal thalli) and another based on the photosynthetic response. Although significant differences were detected in photosynthetic quantum yield and water loss under emersion conditions, with thalli from Punta Calaburras being more affected by emersion than those from Tarifa, the developmental instability showed that the population from Tarifa suffers higher stress during ontogeny than that from Punta Calaburras. In conclusion, this study demonstrates the teleconnection between atmospheric oscillations and survival and proliferation of marine macroalgae.
Keywords: Developmental instability; Fucus guiryi; Stress; North Atlantic Oscillation; Photosynthesis